Study of Correlation between Serum Vitamin B12 Level and Aberrant DNA Methylation in Infertile Males - Dharmendra Kumar; Neeraj K. Agrawal (Indian Journal of Endocrinology and Metabolism, 2024)
Introduction: Altered DNA methylation pattern in sperms has been associated with infertility in males demonstrating defective spermatogenesis or low semen quality. Vitamin B-12, by affecting 1-carbon metabolism pathways, might alter the DNA methylation pattern. We aimed to study the correlation of serum vitamin B12 levels with aberrant DNA methylation in infertile male patients. Methods: A cross-sectional study was conducted on 17 oligozoospermic infertile males (WHO criteria, 2010) and 10 healthy fertile males. Serum vitamin B12 levels were estimated using the chemiluminescence method. Global methylation was determined using the ELISA system (Imprint Methylated DNA Quantification Kit, Sigma–Aldrich). The levels of global DNA methylation were calculated and compared relative to the methylated (100%) control DNA provided with the kit. Results: Mean serum vitamin B12 concentration in the control group was higher than that of the case group. This difference in serum vitamin B12 concentration in both groups was found statistically significant. Although the results of this study show that oligozoospermic men have relatively lower global DNA methylation as compared to normozoospermic control, the values could not reach a statistically significant level. A small positive correlation was found between serum vitamin B12 levels and percent methylation defect (r = 0.14) but was statistically insignificant. Conclusion: Our study concludes that oligozoospermic infertile males have a significant deficiency of vitamin B12 as compared to normozoospermic fertile males. This study did not find any significant difference in global DNA methylation between the two groups. The present study does not suggest any correlation between serum vitamin B12 level and percent DNA methylation.